Forty-two - the answer to the great question of life, the universe and everything - Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2019)
In my last blogpost, I mentioned a frequent resentment of humanists towards DH, namely the opinion that data-driven results are simply meaningless correlations. Where does this attitude come from? Maybe we could find a...